2020
DOI: 10.1371/journal.pone.0230171
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French version of the « Meta-Cognition Questionnaire » for adolescents (MCQ-Af): Evolution of metacognitive beliefs with age and their links with anxiety during adolescence

Abstract: IntroductionThe Meta-Cognitions Questionnaire for Adolescents (MCQ-A) measures individual differences of metacognitive beliefs and monitoring thought to be involved in the onset and maintenance of psychological disorders, especially in those involving anxiety. This assessment tool has been employed in research and clinical settings involving French-speaking adolescents, but appropriate validation has yet to be conducted. This article aims to first validate the francophone version of the MCQ-Af using measures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
2
8
0
4
Order By: Relevance
“…It is worth noting this because numerous metacognition studies have not examined test–retest reliability ( Bacow et al, 2009 ; Larøi et al, 2009 ; Hsu, 2010 ; Cook et al, 2014 ; Martin et al, 2014 ; Bailey and Wells, 2015 ; Fernie et al, 2015 ; Kollmann et al, 2016 ; Kolubinski et al, 2017 ; Alma et al, 2018 ; Caselli et al, 2018 ; Lloyd et al, 2018 ). In addition, the present findings are consistent with some previous studies ( Cartwright-Hatton et al, 2004 ; Wilson et al, 2011 ; Lachat Shakeshaft et al, 2020 ) with respect to the stability of metacognition over the period of time, although the correlation was weak ( r = 0.24–0.34) ( Cartwright-Hatton et al, 2004 ) or unstable for some domains ( r = 0.24–0.90) ( Wilson et al, 2011 ) of the metacognitive questionnaire when comparing with our test–retest ( r = 0.70–0.81). Regarding to the Cronbach’s alpha coefficient, although the results revealed acceptable internal reliability values for both the whole 10 items (α = 0.64) and for the five items of the CMS metacognition (α = 0.63), the exception was the CMS self-judgment accuracy for which Cronbach’s α was 0.59.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…It is worth noting this because numerous metacognition studies have not examined test–retest reliability ( Bacow et al, 2009 ; Larøi et al, 2009 ; Hsu, 2010 ; Cook et al, 2014 ; Martin et al, 2014 ; Bailey and Wells, 2015 ; Fernie et al, 2015 ; Kollmann et al, 2016 ; Kolubinski et al, 2017 ; Alma et al, 2018 ; Caselli et al, 2018 ; Lloyd et al, 2018 ). In addition, the present findings are consistent with some previous studies ( Cartwright-Hatton et al, 2004 ; Wilson et al, 2011 ; Lachat Shakeshaft et al, 2020 ) with respect to the stability of metacognition over the period of time, although the correlation was weak ( r = 0.24–0.34) ( Cartwright-Hatton et al, 2004 ) or unstable for some domains ( r = 0.24–0.90) ( Wilson et al, 2011 ) of the metacognitive questionnaire when comparing with our test–retest ( r = 0.70–0.81). Regarding to the Cronbach’s alpha coefficient, although the results revealed acceptable internal reliability values for both the whole 10 items (α = 0.64) and for the five items of the CMS metacognition (α = 0.63), the exception was the CMS self-judgment accuracy for which Cronbach’s α was 0.59.…”
Section: Discussionsupporting
confidence: 94%
“…Other studies found non-correlation with age, in the similar age ranges of 11–16 years old ( Wilson et al, 2011 ) and 12–17 years old ( Ellis and Hudson, 2011 ). On the other hand, using the same metacognition questionnaire, a significant negative correlation (age range of 13–16 years old) ( Matthews et al, 2007 ) and a positive correlation (age range of 12–18 years old; age range of 13–17 years old) ( Wolters et al, 2012 ; Lachat Shakeshaft et al, 2020 ) were found. As such, these findings further demonstrate the importance of examining metacognitive ability across a broader age range.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The assessment of metacognitive ability has been generally used with self-report questionnaires (Wolters et al, 2012;Lachat Shakeshaft et al, 2020). Self-report questionnaires are easy to administer and frequently used to assess metacognitive ability; however, these self-reports present several limitations, for example, it is difficult to evaluate for people with difficulties in self reference (e.g., autism spectrum disorders) and who are still developing (e.g., adolescence) (Sebastian et al, 2008).…”
Section: Introductionmentioning
confidence: 99%